2006
DOI: 10.1038/sj.ki.5000177
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in renal parenchymal disease: Why is it so resistant to treatment?

Abstract: The association between hypertension and chronic renal disease is well known. The pathogenesis of hypertension in patients with chronic kidney disease (CKD) is complex and multifactorial, which may explain why it is resistant to treatment. The traditional paradigm is that hypertension in CKD is due either to an excess of intravascular volume (volume dependent) or to excessive activation of the renin-angiotensin system in relation to the state of sodium/volume balance (renin-dependent hypertension). This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 71 publications
(63 reference statements)
4
76
0
8
Order By: Relevance
“…27 In particular, tubulointerstitial injuries are generally considered to lead to microvascular damage and renal ischemia, resulting in resistant hypertension. 28 Male sex was an independent variable for postoperative hypertension. Compared with premenopausal women, male sex is known as a risk factor of arteriosclerosis and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…27 In particular, tubulointerstitial injuries are generally considered to lead to microvascular damage and renal ischemia, resulting in resistant hypertension. 28 Male sex was an independent variable for postoperative hypertension. Compared with premenopausal women, male sex is known as a risk factor of arteriosclerosis and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…aTRH may result in microalbuminuria through prolonged increases in glomerular pressure and subsequent renal damage (19). Furthermore, sodium retention and excessive activation of the renin-angiotensin-aldosterone system have been linked to uncontrolled BP in individuals with CKD (20,21). Also, albuminuria is thought to be preceded by systemic endothelial dysfunction (22).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in renal disease, nondipping is the rule, with a prevalence between 74% and 82%. [25][26][27][28][29] Crosssectional observations have demonstrated that nondippers have more severe morphological 30 and functional 31,32 changes than dippers. Fukuda et al 31 studied subjects with biopsy-proven glomerulopathy and found that creatinine clearance (Cl Cr ) was significantly negatively related to the night/day ratios of both sodium excretion and MAP, whereas Farmer et al 32 have shown that the prevalence of nondipping increases with plasma creatinine concentration in patients with chronic renal insufficiency.…”
Section: Nocturnal Blood Pressure Dipping and Sodium Excretionmentioning
confidence: 99%